2003
DOI: 10.1080/00016470310013680
|View full text |Cite
|
Sign up to set email alerts
|

Low-load resistance muscular training with moderate restriction of blood flow after anterior cruciate ligament reconstruction

Abstract: We performed a prospective study to determine the effects of introducing low-load muscular training with moderate restriction of blood flow during the first 16 weeks after reconstruction of the anterior cruciate ligament. 44 subjects (average age 29 (18-52) years) were randomized into a group that trained restriction of blood flow (group R, n = 22) and a group that trained without restriction (group N, n = 22). Both groups followed the same training schedule. Evaluations of knee extensor and flexor torques bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
290
0
22

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(318 citation statements)
references
References 18 publications
6
290
0
22
Order By: Relevance
“…The muscular benefits arising from BFR training are often promoted for cohorts where high mechanical loads may be contraindicated or not possible, including postoperation rehabilitation patients [2,3] and the elderly [9,10]. While the vast majority of BFR research has been conducted using untrained participants, several investigations have also demonstrated muscular benefits from BFR in athletic populations [5,[11][12][13][14][15][16][17].…”
Section: Adaptive Responses and Potential Mechanisms Underpinning Bfrmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscular benefits arising from BFR training are often promoted for cohorts where high mechanical loads may be contraindicated or not possible, including postoperation rehabilitation patients [2,3] and the elderly [9,10]. While the vast majority of BFR research has been conducted using untrained participants, several investigations have also demonstrated muscular benefits from BFR in athletic populations [5,[11][12][13][14][15][16][17].…”
Section: Adaptive Responses and Potential Mechanisms Underpinning Bfrmentioning
confidence: 99%
“…This novel strategy involves the application of an inflatable cuff or tourniquet around a limb (proximal to the muscles being trained), which limits blood delivery to and from contracting muscles. Training with BFR can facilitate muscular changes in clinical populations [2,3] and athletes alike [4,5]. While the physiological mechanisms that underpin adaptive responses to BFR training are not yet fully understood, this form of training is becoming popular as a way to enhance muscular responses without the need for high mechanical loads.…”
Section: Introductionmentioning
confidence: 99%
“…The novel aspect of training with BFR is that substantial improvements in muscular hypertrophy and strength are possible even when using low-loads (20-40% of concentric 1-repetition maximum [1RM]) for both clinical [4] and athletic [5,6] populations. However, while the muscles of the trunk may benefit to some degree from BFR exercise [7], the trunk muscles are unable to be trained under the same conditions as the limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the models of RE most commonly used in disuse atrophic states are flywheel (30)(31)(32)(33)(34), vascular occlusion (VO) (35), and conventional RE consisting of concentric/eccentric or isometric muscle actions (20,36,37). It is important to emphasize that the composition of these types of RE differs in terms of intensity and volume.…”
Section: Magnitude and Functionality Of Different Types Of Resistancementioning
confidence: 99%
“…The few reports available did not measure markers such as phenotypic transitions and primarily concerned individuals subjected to surgical procedures. Ohta et al (35) investigated the effects of RE with or without moderate VO and consisting of isometric muscle actions in subjects subjected to reconstruction of the anterior cruciate ligament 16 weeks after operation. It was observed that the knee extension-trained group with VO showed a 10% decrease in concentric strength at 60°/s, an 8.3% decrease in concentric strength at 180°/s and an 8.7% decrease in isometric strength at 60° of extensor muscles.…”
Section: Resistance Exercise With Vascular Occlusionmentioning
confidence: 99%